Right Ventricular Dysfunction and Failure in Chronic Pressure Overload - Marc A. Simon; Michael R. Pinsky (Cardiology Research and Practice)
Right ventricular (RV) dysfunction is the main cause of death in pulmonary arterial hypertension (PAH). Our understanding of the pathophysiology of RV dysfunction is limited but improving. Methods to better diagnose RV dysfunction earlier and treatments specifically designed to minimize or reverse the remodeling process are likely to improve outcomes. We review the current understanding of RV dysfunction in chronic pressure overload and introduce some novel insights based on recent investigations into pathophysiology, diagnosis, and treatment.